Extraction of Pb2+ using Silica from Rice Husks Ash (RHA) – Chitosan as Solid Phase - Hanandayu Widwiastuti; Ani Mulyasuryani; Akhmad Sabarudin (Chemistry Department, The University of Brawijaya, 2013)
The existence of lead (Pb) compounds in waters can be caused of waste pollution from industrial activities such as dye and battery industries. Lead has toxic characteristic and is able to causing deseases. The levels of Cr(VI) can be decreased by methods such as electroplating, oxidation, reduction, and membrane separation. But this methods require high cost and produce a lot of waste. Furthermore, those methods cannot determine the small concentration of Pb2+. Therefore, solid phase extraction is used because it’s a simple method and can be used to preconcentrate Pb2+ ion.The aim of this study is to create solid phase from nature material as an alternative method to determine Pb2+ in water samples. The solid phase is silica from rice husks ash (RHA) that was modified using chitosan. To achieve that aim, the optimization of silica : chitosan composition was done. The influence of Pb2+ concentration and citric acid concentration was studied to obtain optimum recovery of Pb2+. Interaction between Pb2+ ion and solid phase silica – chitosan could be estimated based on the result.The result showed the optimum composition of silica : chitosan is 65% silica : 35% chitosan with Cation Exchange Capacity (CEC) 0.00455 mek/g. Mass Adsorbed Pb2+for 1 g silica : chitosan 65% is 9.715 mg/g. Optimum recovery of Pb2+ on solid phase extraction is reached at concentration of Pb2+ 10 ppm and citric acid concentration 0.05 M (88.25 % and 81.18 %). This result showed that solid phase extraction using silica – chitosan can be used as an alternative method to determine Pb2+ in water.